Safety and Efficacy of 0.1% Clobetasone Butyrate Eyedrops in the Treatment of Dry Eye in Sjögren Syndrome. Issue 3 (May 2013) - Aragona, Pasquale; Spinella, Rosaria; Rania, Laura; Postorino, Elisa; Sommario, Margherita S.; Roszkowska, Anna M.; Puzzolo, Domenico
Purpose: To study the effects of a low administration rate and low concentration (0.1%) of clobetasone butyrate eyedrops in patients with Sjögren syndrome (SS). Methods: This prospective, double-masked, randomized, placebo-controlled study included 40 subjects divided into 2 treatment groups: group 1 (2% polyvinylpyrrolidone eyedrops and placebo) and group 2 (2% polyvinylpyrrolidone and 0.1% clobetasone butyrate, 1 drop BID). The treatment lasted for 30 days, with visits at enrollment, baseline, day 15, day 30, and after 15 days of treatment discontinuation. At each visit, symptoms questionnaire, tear film break-up time, corneal fluorescein stain, lissamine green stain, conjunctival impression cytology for human leukocyte antigen–DR (HLA-DR) expression, intraocular pressure (IOP) measurement, and fundus examination were performed. Results: No changes in IOP or fundus examination were observed in either group at each time point. Group 1 patients showed at day 30 a statistically significant amelioration of symptoms and reduction of HLA-DR expression. No changes in other parameters were detected. Group 2 patients showed at day 15 a statistically significant improvement of corneal and conjunctival stain versus baseline values and group 1 at the same time; after 30 days the symptoms score was statistically significantly better than baseline values and group 1 at the same time. The HLA-DR expression and the epithelial cells area were statistically significantly reduced versus baseline and group 1 at the same time. Conclusions: Anti-inflammatory therapy is critical for the treatment of SS dry eye. Clobetasone butyrate, at low dosage, proved to be safe and effective in treating this condition.